The effect of environmental neurological components on math performance in unsuccessful female students - Farzaneh Mikaeili Manee; Mitra Taraj; Sheler Abkhiz (University of Hormozgan, 2022)
The aim of this study was to investigate the effect of brain-based learning training on improving the math performance in unsuccessful female students with emphasis on environmental components. In this study, quasi-experimental methods with pre-test and post-test with control group was used. Participants were 30 female students whom selected from the statistical population of second and third grade students of Urmia public primary schools according to the mathematics scores in the second and third grade of elementary school and also the teacher-made test. Due to the descriptive nature of the assessment system, which uses qualitative terms [such as need for more effort, acceptable, good, very good, excellent] instead of grading students, 30 students at the level of need for effort were randomly selected and randomly assigned to experimental and control groups. The parents of the experimental group were trained in brain-based learning during a two-hour session. The learning environment was changed based on the environmental components affecting the brain (light, nutrition, oxygen, color, music, water). The teacher then taught his lessons based on the principles of brain-based learning in 10 sessions. For both groups (experimental and control), KEY-MATH Test of Mathematics were excited in pre-test and post-test. The results showed that brain-based learning training had a significant effect on improving students' mathematical performance in unsuccessful female students.